Corporate Governance Firm Size and Financial Condition Drive Textile Financial Performance: Tata Kelola Korporasi, Ukuran Perusahaan, dan Kondisi Keuangan Mempengaruhi Kinerja Keuangan Industri Tekstil - Nur Ravita Hanun; Aulia Yunika Pradina (Indonesian Journal of Law and Economics Review, 2025)
General Background Financial performance is a critical indicator of corporate sustainability and investor confidence in manufacturing industries. Specific Background Textile companies face fluctuating financial stability, requiring effective governance mechanisms, adequate firm scale, and sound financial conditions to maintain profitability. Knowledge Gap Previous studies show inconsistent findings regarding the combined roles of independent commissioners, firm size, and financial distress in determining financial outcomes within the textile sector. Aims This study analyzes the relationships between independent commissioners, firm size, and financial distress and financial performance of textile firms listed on the Indonesian stock exchange. Results Using quantitative methods with secondary annual reports, purposive sampling of four firms, and multiple linear regression, the findings demonstrate that independent commissioners, larger firm size, and higher Altman Z-score values are positively and significantly associated with return on assets. Novelty The study integrates governance structure, organizational scale, and financial health indicators simultaneously within one empirical model for the textile industry. Implications The results provide evidence that stronger supervision, asset capacity, and healthier financial conditions support stable profitability and inform managerial and investment decisions. Keywords: Financial Performance, Independent Commissioners, Firm Size, Financial Distress, Textile Industry Key Findings Highlights: Board independence aligns with stronger profitability outcomes Larger asset base corresponds with superior returns Healthier Z-score reflects stable corporate condition